2019
DOI: 10.1002/mp.13708
|View full text |Cite
|
Sign up to set email alerts
|

Response characterization of EBT‐XD radiochromic films in megavoltage photon and electron beams

Abstract: Purpose The purpose of this study was to investigate the beam quality dependence of the EBT‐XD radiochromic films for megavoltage photon and electron beam irradiations by studying their spectral response. Dose, dose rate, and interbatch dependencies were investigated as well. Methods EBT‐XD and EBT3 radiochromic films were cut into 5 cm2 × 5 cm2 pieces, placed between solid water phantoms, and irradiated with 6 and 15 MV photon beams, 6 and 10 MV flattening filter free photon beams, and 6 and 20 MeV electron b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 39 publications
1
39
0
Order By: Relevance
“…In order to measure the dose at the entrance, the film sample was placed at the depth of 1.1 mm (WET) and 50 pulses each with 20 μs duration were delivered to the film. Films were scanned 48 h after irradiation using an Epson Expression 10000XL desktop flatbed scanner (Epson Americana Inc., Long Beach, CA, USA) 24 . The calibration curve was established at conventional dose rate using a Mevion S250 ™ clinical proton beam in Washington University in St. Louis 25 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to measure the dose at the entrance, the film sample was placed at the depth of 1.1 mm (WET) and 50 pulses each with 20 μs duration were delivered to the film. Films were scanned 48 h after irradiation using an Epson Expression 10000XL desktop flatbed scanner (Epson Americana Inc., Long Beach, CA, USA) 24 . The calibration curve was established at conventional dose rate using a Mevion S250 ™ clinical proton beam in Washington University in St. Louis 25 …”
Section: Methodsmentioning
confidence: 99%
“…Films were scanned 48 h after irradiation using an Epson Expression 10000XL desktop flatbed scanner (Epson Americana Inc., Long Beach, CA, USA). 24 The calibration curve was…”
Section: B Experimental Characterizationmentioning
confidence: 99%
“…The response of EBT3 and EBT‐XD films has been shown to be independent of beam quality and dose‐rate in megavoltage photon beams, 22,23,39 therefore irradiating films to the same dose level using two entirely different machines is not a concern. Besides, any dose‐rate or beam quality dependence are further mitigated because both machines have a similar beam quality (63.15% with B = 0.35 T vs 63.5% with no magnetic field) and dose rate (650 vs 600 MU/min).…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that the response of both EBT3 and EBT-XD films is batch-dependent, but energy-independent for megavoltage photon beams, including flattening filter free (FFF) beams, and electron beams. [22][23][24] Active ingredient of both EBT3 and EBT-XD film models are "needle-like" lithium pentacosa-10,12-diynoate acid (LiPCDA) monomer crystals in which a linear polymer (poly-PCDA) can grow. The clumps of film monomers are suspended in the active layer with intermolecular distance of 0.4 nm needed for polymerization to occur.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation